Adaptive-optics imaging of human cone photoreceptor distribution - Chui, Toco Yuen; Song, Hongxin; Burns, Stephen A (Journal of the Optical Society of America. A, Optics, image science, and vision, 2008)
We have used an adaptive-optics scanning laser ophthalmoscope to image the cone photoreceptor mosaic throughout the central 10 degrees -12 degrees of the retina for four normal subjects. We then constructed montages of the images and processed the montages to determine cone locations. Cone densities range from approximately 10,000 cones/mm2 at 7 degrees to 40,000 cones/mm2 at 1 degrees . The smallest cones were not resolved in the center of the fovea. From the locations of the cones we also analyzed the packing properties of the cone mosaic, finding that all four subjects had a slight cone streak of increased cone density and that, in agreement with previous studies using different approaches, the packing geometry decreased in regularity from the fovea toward the periphery. We also found variations in packing density between subjects and in local anisotropy across retinal locations. The complete montages are presented for download, as well as the estimated cone locations.